A preliminary study of porous ceramics with carbon black contents - Haji Azlan, Umar Al-Amani; Jalaluddin, Mohamed Lokman; Abd Rashid, Mohd Warikh (AIMS Press, 2023)
This paper is a study of porous ceramics from a mixture of clay (kaolinite), silica (silicon dioxide), and feldspar by adding the carbon black (CB) with different contents. The results were presented in terms of apparent porosity, relative density, microstructure and porous characteristic, flexural strength and phase formation. As observed, the sintering at 1200 oC is the optimum temperature in this work. In comparison to the samples without CB content, the apparent porosity and relative density of ceramics are highly dependent on the CB contents. This might be attributed to the presence of porous structure as seen in SEM images on the fracture surface of ceramics. It also revealed that the addition of CB resulted in smaller pore sizes and a more uniform pore distribution. The creation of pores in porous ceramics was mainly attributed to the loss of shape of CB microspheres at high temperatures, as observed from SEM. The flexural strength of the sintered samples exhibited an average decrease from 60 to 55 MPa due to the presence of CB, which is typically known to reduce the mechanical properties with high porosity. In XRD results, the muscovite phase is represented by a few of peaks with significant intensities, while the rest peaks are of undetermined phase. The strongest peak at a 26 of 2θ angle, suggesting the presence of potassium and aluminium in the form of silicate minerals.